The Form of the Good in Plato’s Timaeus - Gkatzaras, Thanassis (PLATO JOURNAL, 2018)
The purpose of this paper is to provide evidence that the Form of the Good (as we know it from the Republic) is still present in the Timaeus and is ontologically independent from the Demiurge and his Paradigm. This claim is supported by selected passages from Timaeus’ text, but it is also based on Phaedo’s theory of causation and on the simile of the sun in Republic. It is also highlighted after a detailed comparison between the philosopher-kings and the Demiurge, and after the emergence of their striking similarities.